Two new endophytic Colletotrichum species from Nothapodytes pittosporoides in China - Sixuan Zhou; Lijun Qiao; Ruvishika S. Jayawardena; Kevin D. Hyde; Xiaoya Ma; Tingchi Wen; Jichuan Kang (MycoKeys, 2019)
Two new endophytic species, Colletotrichum jishouense sp. nov. and. C. tongrenense sp. nov. were isolated from Nothapodytes pittosporoides in Guizhou and Hunan provinces, China. Detailed descriptions and illustrations of these new taxa are provided and morphological comparisons with similar taxa are explored. Phylogenetic analysis with combined sequence data (ITS, GAPDH, ACT and TUB2) demonstrated that both species formed distinct clades in this genus. This is the first record of Colletotrichum species from N. pittosporoides in China.